(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The country has experienced significant business and economic growth as a result of the rise in the number of women entrepreneurs. By creating jobs in the nation, influencing demographic changes, and motivating the subsequent generation of female founders, women-owned businesses are playing a significant role in society. Startup India is dedicated to fostering women’s entrepreneurship in India through initiatives, programmes, the development of enabling networks and communities, and the activation of partnerships among various stakeholders in the startup ecosystem. This commitment is part of the organization’s vision to support the sustainable development of women entrepreneurs for the nation’s balanced growth. The present study is to assess the Performance of Pradhan Mantri Mudra Yojana in Kancheepuram District of Tamil Nadu. The study was carried out in Tamil Nadu’s Kancheepuram District of Tamil Nadu with the help of both primary and secondary data. Kancheepuram district was chosen as the study area because it is one of Tamil Nadu’s top districts for agricultural development. Ten localities in Kancheepuram were chosen at random for the study. Data collection areas have been covered for those who have used loan services under the PMMY scheme in the study area. It is found that the perception levels of women entrepreneurs have been divided into three categories: good, fair, and poor. The 129 samples (64.50 percent) are inferred to have good perception, and the 40 samples (20 percent) are inferred to have fair perception. The study’s remaining 31 respondents (15.50 percent) have a negative perception of the PMMY scheme. Therefore, the PMMY scheme has given women entrepreneurs in the Kancheepuram District a positive perception.